Isolasi dan Karakterisasi Amilase dari Kapang Alkalotoleran Asal Limbah Cair Tapioka - Nisa Rachmania Mubarik; Evi Damayanti; Sri Listyowati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
A total of 6 fungi isolates of growing at pH 9 and 2 isolates on pH 10 with amylolytic indexes 0f 0.07-1.42 have been isolated from cassava starch liquid waste. Two isolates having the highest amylolytic index were identified as Aspergillus sydowii K10 (1.42) and Aspergillus versicolor L30 (1.4). Both A. sydowii K10 and A. versicolor L30 were described as alcalotolerant for being able to grow with range pH 5-10. The optimal -amylases production of A. sydowii K10 and A. versicolor L30 was obtained after 4 and 3 days of incubation at 300C. The optimum of -amylase activity from A. sydowii K10 was at 400C and 700C, and pH 6; while those from A. versicolor L30 was at 500C and pH 6 respectively. Both A. sydowii K10 and A. versicolor L30 could produce glucoamylase. The optimum of glucoamylase activity from A. sydowii K10 was at 400C and pH 5, while those from A. versicolor L30 was at 500C and pH 5 respectively.